A Study of Nutrient Foramina of Humerus at Chhattisgarh State - Khandve, Dr. Bhavana; Verma, Dr. Ambrish (International Journal of Innovative Research in Medical Science, 2018)
Introduction Nutrient foramen is an opening in the bone shaft which allows passage to the blood vessels of the modularly cavity of a bone for its nourishment and growth.[1] The nutrient artery enters individual bones obliquely through a nutrient foramen.[2] The nutrient artery is the principal source of blood supply to a long bone and nutrient foramen is an opening in the bone shaft which gives passage to the particularly important during its active growth period in the embryo and fetus, as well as during the early phase of ossification.[3] Nutrient foramen are directed towards elbow in upper limb (directed towards lower end of humerus and upper ends of radius and ulna), while in lower limb nutrient foramen is directed away from knee (that is, upper end for femur and lower ends of tibia and fibula). This is said to be due to one end of limb bones growing faster than the other and generally follows the rule, “to the elbow I go, from the knee I flee.” Their positions in mammalian bones are variable and may alter during the growth phase. The topographical knowledge of these nutrient foramina is useful in operative procedures to preserve the circulation[4-6] Nutrient artery is the major source of blood supply to bone and it plays an important role in healing of fracture, Orthopedic surgical procedures like vascularized bone microsurgery requires the detailed knowledge of the blood supply. In vascular bone grafting, the blood supply by nutrient artery is extremely important and must be preserved in order to promote fracture healing.[7] Humphrey was working on the direction and obliquity of nutrient canals postulated periosteal slipping theory, the canal finally directed away from the growing end.[8] Fracture healing or hematogenic osteomyelitis is closely related to the vascular system of the bone.[9] Study of nutrient foramina in upper limb is very important for morphological, clinical, and pathological point of view. Detailed data on the blood supply to the long bones is invariably crucial in the development of new transplantation and resection techniques in orthopedics.[10] Humerus is the largest and longest bone of the upper limb. It is supplied by nutrient artery which is a branch of brachial artery. The nutrient artery enters the bone through nutrient foramen located on antero-medial surface a little below its midpoint which is directed downwards and opens close to the medial border.[11]